2001
DOI: 10.1038/sj.gene.6363734
|View full text |Cite
|
Sign up to set email alerts
|

Class II HLA associations with autoantibodies in scleroderma: a highly significant role for HLA-DP

Abstract: Scleroderma is a condition of variable phenotype characterised by fibrosis of the skin and internal organs. There is a range of disease-specific autoantibodies found in the sera of patients. The aims of this study were to: (1) investigate the role of the MHC and particularly HLA-DP in the production of autoantibodies; (2) investigate clinical associations with autoantibodies. We have performed HLA class II typing using PCR with sequence-specific primers on DNA samples from 202 scleroderma patients and 307 UK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
64
4
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 31 publications
9
64
4
5
Order By: Relevance
“…We have recently shown that the production of another major autoantibody found in scleroderma patients, antitopoisomerase, is tightly linked both to the presence of fibrosis and to the HLA class II alleles DRB1*1101/04 and DPB1*1301 (14). However, we and other investigators have found only weak associations between DRB1*0101 and DQB1*05 and the production of ACA (15)(16)(17).…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…We have recently shown that the production of another major autoantibody found in scleroderma patients, antitopoisomerase, is tightly linked both to the presence of fibrosis and to the HLA class II alleles DRB1*1101/04 and DPB1*1301 (14). However, we and other investigators have found only weak associations between DRB1*0101 and DQB1*05 and the production of ACA (15)(16)(17).…”
mentioning
confidence: 40%
“…Partial support for this comes from Kuwana et al, who reported that antibodies to HLA-DR and HLA-DQ blocked antitopoisomerase production in vivo (29). However, this leaves our HLA-DP association unexplained (14), since DP and TNF are not in linkage disequilibrium, and antibodies to DP did not block antitopoisomerase production in the system of Kuwana et al…”
Section: Discussionmentioning
confidence: 89%
“…There are three predominant antibodies: anticentromere antibodies, antitopoisomerase antibodies (ATAs), and anti-RNA polymerase antibodies. These autoantibodies are almost totally mutually exclusive and define different clinical subsets of the disease with reasonable accuracy [83,84]. In particular, the presence of ATAs (also known as anti-Scl-70 antibodies) in a scleroderma patient is very strongly associated with the risk of development of pulmonary fibrosis (relative risk 17) [83,84].…”
Section: Pulmonary Fibrosis In Systemic Sclerosismentioning
confidence: 99%
“…The majority of SSc patients produce antibodies directed at nuclear antigens, which are strongly associated with organ involvement and disease outcome. [9][10][11][12] Although the etiology of SSc is unknown, genetic factors are thought to be important. Several polymorphic genes-which are either risk factors for the development of SSc or influence disease-associated autoimmune responsiveness-have been identified.…”
mentioning
confidence: 99%